GROWTH RATE DISTRIBUTION OF BORAX SINGLE CRYSTALS ON THE (001) FACE UNDER VARIOUS FLOW RATES - Suharso Suharso (Indonesian Journal of Chemistry, 2006)
The growth rates of borax single crystals from aqueous solutions at various flow rates in the (001) direction were measured using in situ cell method. From the growth rate data obtained, the growth rate distribution of borax crystals was investigated using Minitab Software and SPSS Software at relative supersaturation of 0807 and temperature of 25 °C. The result shows that normal, gamma, and log-normal distribution give a reasonably good fit to GRD. However, there is no correlation between growth rate distribution and flow rate of solution.